Magnetotactic Bacteria and Magnetosomes as Smart Drug Delivery Systems: A New Weapon on the Battlefield with Cancer? - Danuta Kuzajewska; Agata Wszołek; Wojciech Żwierełło; Lucyna Kirczuk; Agnieszka Maruszewska (Biology, 2020)
An important direction of research in increasing the effectiveness of cancer therapies is the design of effective drug distribution systems in the body. The development of the new strategies is primarily aimed at improving the stability of the drug after administration and increasing the precision of drug delivery to the destination. Due to the characteristic features of cancer cells, distributing chemotherapeutics exactly to the microenvironment of the tumor while sparing the healthy tissues is an important issue here. One of the promising solutions that would meet the above requirements is the use of Magnetotactic bacteria (MTBs) and their organelles, called magnetosomes (BMs). MTBs are commonly found in water reservoirs, and BMs that contain ferromagnetic crystals condition the magnetotaxis of these microorganisms. The presented work is a review of the current state of knowledge on the potential use of MTBs and BMs as nanocarriers in the therapy of cancer. The growing amount of literature data indicates that MTBs and BMs may be used as natural nanocarriers for chemotherapeutics, such as classic anti-cancer drugs, antibodies, vaccine DNA, and siRNA. Their use as transporters increases the stability of chemotherapeutics and allows the transfer of individual ligands or their combinations precisely to cancerous tumors, which, in turn, enables the drugs to reach molecular targets more effectively.